The Role of Non-Oil Revenues in Achieving Financial Sustainability for the General Budget in Iraq - Al-Nassar, Amjed Jasim Naeemah (Research Parks Publishers, 2025)
This study examines the role of non-oil revenues in achieving fiscal sustainability for the general budget in Iraq. Data were collected from the World Bank database, and the study sample covered Iraq during the period (2019-2023). Random effects panel data models were run to compare the study hypothesis. The results indicate that non-oil revenues are a key factor in enhancing fiscal sustainability, through reducing the structural deficit and achieving a more flexible and stable structural fiscal balance. There is also a relationship between the growth of non-oil revenues and a decline in the public debt-to-GDP ratio, reflecting the vital role of these revenues in controlling debt. This study provides evidence that the increase in non-oil revenues during years (2019-2023) contributed to reducing the budget deficit gap, especially in light of oil price volatility, providing public finances with relative flexibility in covering current expenditures. This study provides numerous pieces of evidence and guidelines related to diversifying revenue sources, which reduces the inequality and class differences resulting from the unequal distribution of oil revenues. It also ensures that all citizens contribute to and benefit from the financial system. Non-oil revenues are used to finance education, health, and infrastructure, contributing to raising social welfare, reducing poverty, and improving the treatment of unemployment. Few previous studies have addressed the relationship between non-oil revenues and financial sustainability, and this study aims to fill this knowledge gap. This study may also help relevant authorities in Iraq understand the level of non-oil revenues and how they appropriately impact financial sustainability, which will help improve revenue levels in line with the nature of the state's work and principles.